Gestión administrativa y su relación con el desempeño docente (MBDD) en una Institución Educativa Privada de Lima, 2021. - Guzmán Barreto , Lacey Catherine (2023)
In the present study, the connection between administrative management and teaching performance in an Educational Institution in Lima is analyzed. Quantitative descriptive correlational research, cross-sectional and with a non-experimental design. The Sample was 50 teachers. To collect data, two Likert-type assessment scales are designed, with two instruments for each variable, which consists of 32 items each based on four dimensions. The results indicate a direct and significant relationship between administrative management and teacher performance. It is concluded through the analysis that there is a relationship between both variables, and administrative management is essential for school organization and the efficient and effective fulfillment of responsibilities and functions of each member, which translates into better results for society.